Experimental study on effect of system pressure on two-phase flow pressure drop at sub-atmospheric conditions. (2020) - Saxena, Vivek; Deswal, Harsh; Pattanayak, Bikash; Kothadia, Hardik
Abstract: The objective of the present work is to study two phase flow pressure drop in a helically coiled once through steam generator under sub-atmospheric conditions. Literature survey on two-phase flow pressure drop in a helical coil reveals that most of the research articles correspond to studies under high pressure and only few data are available for sub-atmospheric pressure conditions. In this study, an experimental investigation is carried out for a helically coiled tube of tube diameter 9.5 mm, coil diameter 282.7 mm and tube length 5330 mm. System is operated at sub-atmospheric pressure of 150 mbar and atmospheric pressure, respectively. Water and/or steam mass flow rate through the steam generator are taken at 36 kg/h, 54 kg/h and 72 kg/h. A 50 kW capacity DC power supply is used to supply required heat for steam generation. Experiment is carried out for power input ranging from 10 kW to 30 kW. The steam quality at helical coil exit is kept near to 0.5 and hence the power input is decided by amount of heat required to convert liquid water at inlet temperature to saturated vapour-liquid mixture with vapour quality of 0.5. The liquid to steam density ratio ranges from 7500 to 16000. In this study it is observed that the pressure drop at sub-atmospheric pressure is high as compared to atmospheric pressure.